The ecosystem for organized crime: HEUNI 25th anniversary lecture, 7th Inkeri Anttila lecture Helsinki, Finland; lecture given: October 5, 2006 - Felson, Marcus (HEUNI papers, 2006)
The intellectual study of organized crime suffers from at least four major distractions: (a) mixing overall analysis with the requirements of prosecution, (b) understating the diversity of criminal cooperation, (c) underestimating how crime cooperation interacts with legitimate activities, and (d) overestimating the degree of planning and sophistication needed for offender symbiosis to occur. This paper draws from the life sciences to analyze criminal cooperation in full diversity, yet with greater clarity. In the process, the author produces twelve principles to help understand “the web of criminal cooperation.” The author distinguishes public, semipublic, semiprivate, and private aspects of criminal cooperation, and emphasizes the dependence of organized crime on the failure to manage public space.